Evaluasi Manajemen Risiko Pelaksanaan Konstruksi Gedung Rumah Sakit Umum Daerah Kabupaten Paniai Provinsi Papua - Intan Yunita Datu Mangngiri; Syahril Taufik (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
This paper discusses the analysis in evaluating the risk management of hospital building construction using the Analytic Hierarchy Process (AHP) model as a method for analyzing the level of risk in relation to controlling the quantity and quality of each structural work item. There are at least 7 (seven) factors considered as AHP inputs, namely time, method of implementation, labor, equipment, materials, administration, cost, and design. This study method includes data collection methods and analytical methods. For data collection, this study uses a questionnaire method which contains questions related to technical and non-technical factors used to assess work effectiveness from a risk management perspective. The results of the analysis of hospital construction risk management show that the highest level of risk occurs in the material and environmental aspects. Risk handling should be done by the method of changing and coping to the high risk activities. Keywords: risk management, AHP, hospital, construction materials, workforce